Exploring Management Research Landscape in Indonesia - Harsanto, Budi; Firmansyah, Egi Arvian (JDM (Jurnal Dinamika Manajemen), 2021)
Management research is critical to the advancement of management studies and practice in Indonesia. The aim of this study is to explore the landscape of management research in Indonesia. This study uses a bibliometric approach with data collected from the international academic database. In our analysis, among others, we refer to the classical categorization of business functions and macro clusters or special interest groups from leading management associations. The study results show that the management research landscape in Indonesia can be grouped into six categories, namely ‘operations management’, ‘financial management, ‘marketing management’, ‘human resource management, ‘strategy and entre- preneurship’, and ‘performance and governance’. This is the first study that explores the management research landscape in the Indonesian context..